PRESERVING LOCAL ORNAMENT THROUGH ALGORITHM - Aswin Indraprastha; Zulhadi Sahputra; Agus Suharjono (Jurnal Ilmu Komputer dan Informasi, 2013)
This study employs fractal algorithms to generate and transform original Aceh ornaments into architectural design elements. The interpretation and generation of this ornaments by fractal method uses L-system based software called jBatik. We studied an approach of preserving local ornaments using three stages: understanding the local ornament geometry function, interpreting and generating new ornament using fractal method, exploring the possible iterations of patterns based on fractal algorithms. We applied this process into architectural design experiments where the 3D patterns used as an architectural design elements. The result shows that the possibility of preserving local ornament by fractal method can open opportunity for architects to explore new approach in design using the iteration and transformation of local ornaments. The endless possibilities offered by fractal method for generating new ornaments justify the digital advancement for its preservation.